Multi-Center Randomized Phase II Clinical Trial on Remote Ischemic Conditioning in Acute Ischemic Stroke Within 9 Hours of Onset in Patients Ineligible to Recanalization Therapies (TRICS-9): Study Design and Protocol - Diamanti, Susanna; Beretta, Simone; Tettamanti, Mauro; Sacco, Simona; Sette, Giuliano; Ornello, Raffaele; Tiseo, Cindy; Caponnetto, Valeria; Beccia, Mario; Alivernini, Diletta; Costanzo, Rocco; Ferrarese, Carlo (Frontiers in Neurology, 2021)
Aim: To assess the efficacy of remote ischemic conditioning (RIC) in patients with ischemic stroke within 9 h of onset, that are not candidates for recanalization therapies. Sample Size Estimates: A sample size of 80 patients (40 in each arm) should yield 80% power to detect a 20% difference in early neurological improvement at 72 h at p = 0.05, two sided. Methods and Design: TRICS-9 is a phase II, multicenter, controlled, block randomized, open-label, interventional clinical trial. Patients recruited in Italian academic hospitals will be randomized 1:1 to either RIC plus standard medical therapy or standard medical therapy alone. After randomization, RIC will be applied manually by four alternating cycles of inflation/deflation 5 min each, using a blood pressure cuff around the non-paretic arm. Study Outcomes: The primary efficacy outcome is early neurological improvement, defined as the percent change in the National Institute of Health Stroke Scale (NIHSS) at 72 h in each arm. Secondary outcomes include early neurologic improvement at 24 and 48 h, disability at 3 months, rate of symptomatic intracerebral hemorrhage, feasibility (proportion of patients completing RIC), tolerability after RIC and at 72 h, blood levels of HIF-1α, and HSP27 at 24 h and 72 h. Discussion/Conclusion: RIC in combination with recanalization therapies appears to add no clinical benefit to patients, but whether it is beneficial to those that are not candidates for recanalization therapies is still to be demonstrated. TRICS-9 has been developed to elucidate this issue. Clinical Trial Registration:ClinicalTrials.gov, identifier: NCT04400981.